A Psychoanalysis of The Main Characters Aladdin and Jasmine in The Aladdin Movie (2019) - Artamevia, Adellia; Agnes Widyaningrum (Universitas Cokroaminoto Palopo, 2024)
Psychoanalysis is one of the theories in the literature which is usually used to study personality in humans. The purpose of this research is to find out and describe the imaginary, symbolic, and real aspect of Lacan’s psychology theory reflected by the main characters of Aladdin movie (2019). This research used context oriented approach. The analysis was started by identifying the Imaginary, Symbolic, and Real by Jacques Lacan. After identifying, then classifying the Imaginary. Symbolic, and Real aspects reflected by the main characters, next the researcher interpreting the findings. The results of the analysis are the researcher found 1 data included in the Imaginary aspect, 7 data included in the Symbolic aspect, and 3 data included in the Real aspect. The conclusions of this analysis are all aspects of Jacques Lacan's psychoanalysis reflected by the main characters in the Aladdin movie (2019), and Symbolic is the most frequently found aspect, all of which are almost influenced by Aladdin's desires.